Screening of Anti Diuretic Activity Aerva Lanata Extracts against Furosemide Exposed Rodent Models - N. Shyam Sundar; P. Dhasarathan; K. R. Narayanan; M. Thenmozhi (New Visions in Biological Science Vol. 8, 2022)
Bioactive compounds of aromatic and medicinal plants were showed remarkable activity against bacteria and fungi. Medicinal plants were used to inhibit the pathogens and cure most of the diseases like diuretics and diabetics etc., Hence in the present study investigated antidiuretic activity of the Aerva lanata was analysed and discussed. In this study, total urine output in normal animas were showed 1.32±0.22 ml/kg of animal per day, but diuretic animal have 1.76 ± 0.26 ml/kg/day. It was increased 44% and stimulated the action of diuretic 1.5 fold in this study. Furosemide (Standard diuretic drug) induced percentage secretion of saline was 8.52±0.56 and urine excretion was 7.38±0.53. The active compound of Aerva lanata was showed to reduce the remarkable and reach the control value and showed antidiuretic efficiency. Total urine output in diuretic induced animal treated with 2-Decyl -1-tetra decanol was 1.30 ±0.27 ml/kg of animal per day compared to control (1.32±0.22 ml/kg of animal per day) it was decreased 2% and stimulated the action of diuretic 1 fold. The active compound of A. Lanata, 2-Decyl -1-tetra decanol induced percentage of secretion of saline was 8.76±0.52 and urine excretion was 7.49±0.48. The standard antidiuretic hormone also showed similar value of active compounds of Aerva lanata. From the investigations the Aerva lanata to be used effective cheap plant based drug for diuretic diseases.